2008
DOI: 10.1038/sj.jid.5701147
|View full text |Cite
|
Sign up to set email alerts
|

Premature Senescence of Balding Dermal Papilla Cells In Vitro Is Associated with p16INK4a Expression

Abstract: Androgenetic alopecia (AGA), a hereditary disorder that involves the progressive thinning of hair in a defined pattern, is driven by androgens. The hair follicle dermal papilla (DP) expresses androgen receptors (AR) and plays an important role in the control of normal hair growth. In AGA, it has been proposed that the inhibitory actions of androgens are mediated via the DP although the molecular nature of these interactions is poorly understood. To investigate mechanisms of AGA, we cultured DP cells (DPC) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
115
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 47 publications
5
115
0
2
Order By: Relevance
“…Recent studies reported a dermal stem cell depletion with aging 53 and a premature senescence of the dermal papilla cell in balding scalps. 54 Nevertheless, what could be the role of TAp63 in these processes? What would be the optimal level of manipulation of TAp63 in the SKPs as we age?…”
Section: In Tap63mentioning
confidence: 99%
“…Recent studies reported a dermal stem cell depletion with aging 53 and a premature senescence of the dermal papilla cell in balding scalps. 54 Nevertheless, what could be the role of TAp63 in these processes? What would be the optimal level of manipulation of TAp63 in the SKPs as we age?…”
Section: In Tap63mentioning
confidence: 99%
“…Though siblings carry the genes, there are more collaborators than just the presence of DHT to manifest miniaturization and present the clinical characteristics of AGA. Works of Headington, Philpott, Farjo N, Farjo B and Bahta have indicated that the multiple pathways of hair loss are in fact, interlinked, overlapping and in over 33% of the cases there may not be any identifiable cause [6,28] . DHT has been considered to be a cause for hair loss but it is uncommon to find raised DHT levels in patients and there is no correlation between DHT levels and the grade of hair loss manifested in the patients [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DP cells in the balding scalp grow more slowly in vitro, compared with cells from the non-balding scalp. The reduced proliferative activity of balding DP cells is associated with changes in the expression levels of senescence-associated (SA) β-galactosidase, oxidative stress markers, superoxide dismutase and catalase (20). These findings indicate that oxidative stress is important in the loss of DP cells and in hair production.…”
Section: Introductionmentioning
confidence: 69%